2012
DOI: 10.1371/journal.pone.0033276
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Amyloid Peptides Enhance the Proliferative Response of Activated CD4+CD28+ Lymphocytes from Alzheimer Disease Patients and from Healthy Elderly

Abstract: Alzheimer's disease (AD) is the most frequent form of dementia among elderly. Despite the vast amount of literature on non-specific immune mechanisms in AD there is still little information about the potential antigen-specific immune response in this pathology. It is known that early stages of AD include β-amyloid (Aβ)- reactive antibodies production and inflammatory response. Despite some evidence gathered proving cellular immune response background in AD pathology, the specific reactions of CD4+ and CD8+ cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 58 publications
(67 reference statements)
1
18
0
Order By: Relevance
“…In Alzheimer's disease the peripheral lymphocytes respond poorly to mitogenic stimulation. The same phenomenon was found in chronic schizophrenia [14][15][16]. This may open a diagnostic window for early detection and prevention of these conditions (first pillar of interventions).…”
Section: Maintenance Treatment Of Chronic Psychosis: the Second Pillasupporting
confidence: 60%
“…In Alzheimer's disease the peripheral lymphocytes respond poorly to mitogenic stimulation. The same phenomenon was found in chronic schizophrenia [14][15][16]. This may open a diagnostic window for early detection and prevention of these conditions (first pillar of interventions).…”
Section: Maintenance Treatment Of Chronic Psychosis: the Second Pillasupporting
confidence: 60%
“…Others have also observed no correlation of activated CD4 T cells with a battery of cognitive domain tests in aMCI subjects ( n = 19) [ 29 ]. It is thought that T cells in the CSF would typically mediate an Aβ 42 -directed immune response to clear amyloid from the brain [ 37 ], which should result in improved cognition and brain health. However, the aMCI cohorts in our study or the Lueg study do not support this concept.…”
Section: Discussionmentioning
confidence: 99%
“…Richart-Salzburger, for example, reported a significant decrease of CD3 + CD8 + and CD19 + lymphocytes in the peripheral blood of Alzheimer’s disease patients, suggesting a general decline of the adaptive immunity in disease pathogenesis [ 31 ]. Other authors, in contrast, observed significant increases in activated CD4 + and CD8 + T cell subsets in peripheral blood [ 32 35 ]. Recently, Lueg et al also assessed alterations of T cell subsets in the intrathecal compartment of cognitively impaired and cognitively intact elderly subjects as well as healthy younger control individuals and found a significantly increased proportion of CD8 + lymphocytes in the CSF of patients with Alzheimer’s disease – but not in patients suffering from other dementias – which correlated with cognitive deficits [ 33 ].…”
Section: Introductionmentioning
confidence: 92%